NAD(+) hydrogenation on Au electrode deposited on modified glassy carbon - Rahman, Gul; Lim, Ji Yeon; Jung, Kwang-Deog; Joo, Oh-Shim (ELSEVIER SCIENCE INC, 2010)
Gold nanoparticles(AuNP) were electrodeposited on a glassy carbon(GC) which was electrochemically modified by potentiodynamic cyclic polarization in acidic medium. The AuNP deposits were characterized by scanning electron microscopy, cyclic voltammetry, chronoamperometry and linear sweep voltammetry. Results of these studies showed that very small sized AuNP are deposited with significantly high particle density which is attributed to the surface modification of GC. The resulted AuNP/GC electrode showed high catalytic activity for electrochemical reduction of NAD(+) to NADH, indicating its potential for electrocatalytic applications. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: GOLD NANOPARTICLES; SIZE; REDUCTION; ACTIVATION; MONOLAYERS; CATALYSIS; GRAPHITE; BEHAVIOR; OXIDES; FILMS